Silver-copper-based thermoelectric material and preparation method thereof
Patent Information
- Application Number
- CN202610958829.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-13
AI Technical Summary
然而,Ag2Q材料受限于n型导电特征,无法满足柔性器件对p型材料的匹配需求
1.本发明在Ag2-xCuxS1-y-zSeyTez体系中的阳离子位引入Cu元素,为实现导电类型的精准调控奠定了关键的材料基础。区别于传统Ag2Q基材料的n型导电特性,本发明通过引入Cu元素提供空穴载流子来源,并结合对阴离子位组分比例(即x,y,z的取值)的精确协同调控,成功实现了体系导电类型向p型的转变。此外,在特定的配比区间内,该体系亦可表现出n型特性。Cu元素的引入及多元素的协同合金化成功拓宽了该类材料的导电类型,实现了p型热电材料的可靠制备。
Smart Images

Figure CN122897685A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermoelectric materials technology, specifically relating to a silver-copper based thermoelectric material and its preparation method. Background Technology
[0002] Thermoelectric materials are functional materials capable of directly converting heat energy into electrical energy. Based on the Seebeck and Peltier effects, they have broad application prospects in waste heat recovery power generation and solid-state refrigeration. The core indicator for evaluating the performance of thermoelectric materials is the dimensionless thermoelectric figure of merit (ZT), defined as ZT = S 2 σT / κ (in T Absolute temperature σ For electrical conductivity, S For Seebeck coefficients, κ (For thermal conductivity). In recent years, chalcogenide silver-based semiconductors, represented by Ag₂Q (Q=S, Se, Te), have exhibited extremely low lattice thermal conductivity while also possessing room-temperature plastic deformation capabilities rarely seen in traditional inorganic thermoelectric materials, providing a new technological path for the development of flexible thermoelectric devices. However, Ag₂Q materials are limited by their n-type conductivity characteristics and cannot meet the matching requirements of flexible devices for p-type materials. Constructing an AgCuQ system can achieve a p-type transition, but existing high-temperature melting processes easily induce the volatilization of chalcogen elements when preparing this multi-element system, leading to product composition deviation, severe phase separation, and deterioration of thermoelectric performance. Furthermore, this process is energy-intensive. Therefore, it is urgent to explore a near-room-temperature, high-efficiency preparation process, distinct from traditional melting routes, to prepare p-type plastic silver-copper-based thermoelectric materials, in order to achieve low-cost, mass production of high-performance p-type plastic thermoelectric materials. Summary of the Invention
[0003] The purpose of this invention is to provide a silver-copper based thermoelectric material and its preparation method. The silver-copper based thermoelectric material provided by this invention possesses excellent thermoelectric properties.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a silver-copper based thermoelectric material with the chemical formula Ag. 2-x Cu x S 1-y-z Se y Te z , where 0 < x <2; 0≤ y ≤1; 0≤ z ≤1; 0< y + z ≤1.
[0005] Preferably, the x The value is 0.5~1.5.
[0006] Preferably, the z Greater than 0 and less than 1.
[0007] The present invention also provides a method for preparing the silver-copper based thermoelectric material described in the above technical solution, comprising: The raw materials were subjected to high-energy ball milling and sintering to obtain silver-copper based thermoelectric materials.
[0008] Preferably, the raw materials include inorganic raw materials and process control agents.
[0009] Preferably, the grinding balls used in the high-energy ball mill include large balls and small balls; the particle size ratio of the large balls to the small balls is (1.3~3):1.
[0010] Preferably, the ratio of the number of large balls to the number of small balls is 1:(1~8).
[0011] Preferably, the large spheres have a particle size of 8-15 mm; the small spheres have a particle size of 3-7 mm.
[0012] Preferably, the sintering includes hot pressing sintering or spark plasma sintering.
[0013] Preferably, the sintering mold used in the sintering process has an insulating medium on the contact surface with the sample to be sintered.
[0014] This invention provides a silver-copper based thermoelectric material with the chemical formula Ag. 2-x Cu x S 1-y-z Se y Te z , where 0 < x <2; 0≤ y ≤1; 0≤ z ≤1; 0< y+z ≤1. This invention, through the synergistic design of multiple anion and cation sites, regulates the crystal and phase structures of the system, effectively reducing the lattice thermal conductivity of the material and providing a structural basis for the material to exhibit intrinsic room-temperature plasticity. Furthermore, the use of a high-energy ball milling process overcomes the problem of chalcogenide volatilization and phase separation caused by traditional high-temperature processes. Ultimately, this invention successfully prepared a plastic p-type thermoelectric semiconductor material and achieved an effective improvement in thermoelectric transport performance. Experimental results show that the ZT value of the silver-copper based thermoelectric material provided by this invention is 0.11~0.50 at room temperature. Attached Figure Description
[0015] Figure 1 BSE image of the silver-copper based thermoelectric material prepared in Example 7; Figure 2 EDS surface scan image of the silver-copper based thermoelectric material prepared in Example 7; Figure 3 The XRD patterns of the silver-copper-based thermoelectric materials prepared in Examples 7-8 are shown below. Figure 4 The data are multi-point EDS composition analysis data of the silver-copper based thermoelectric material prepared in Example 7; Figure 5 BSE image of the silver-copper based thermoelectric material prepared in Example 8; Figure 6 BSE image of the silver-copper based thermoelectric material prepared in Example 16; Figure 7 This is an EDS surface scan image of the silver-copper based thermoelectric material prepared in Example 16. Detailed Implementation
[0016] This invention provides a silver-copper based thermoelectric material with the chemical formula Ag. 2-x Cu x S 1-y-z Se y Te z , where 0 < x <2; 0≤ y ≤1; 0≤ z ≤1; 0< y + z ≤1.
[0017] In this invention, the x Preferably, it is 0.5 to 1.5. As one embodiment, the... x It can be 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3 or 1.4.
[0018] As one implementation method, the y It can be 0.04, 0.1, 0.2, 0.22, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9.
[0019] In this invention, the z Preferably, the value is greater than 0 and less than 1. As one implementation method, the... z It can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.85 or 0.9.
[0020] As one implementation method, the silver-copper based thermoelectric material can be AgCuS 0.08 Se 0.22 Te 0.7 or AgCuS 0.05Se 0.1 Te 0.85 .
[0021] Traditional inorganic silver-based chalcogenide thermoelectric materials (such as Ag₂Se and Ag₂Te) intrinsically exhibit n-type conductivity, making it difficult to find p-type thermoelectric arm materials with matching performance when constructing flexible thermoelectric devices. Furthermore, multi-element silver-copper-based systems are prone to localized compositional segregation and precipitation of non-plastic second phases during thermal processes, and some matrix materials exhibit typical brittle characteristics, failing to meet the reliability requirements of flexible thermoelectric devices in complex service environments. To address these issues, this invention introduces Cu elements at cation sites to regulate the crystal structure and phase composition of the system; however, simply introducing Cu (such as pure AgCuSe) is insufficient to change its n-type conductivity. Further research revealed that significant substitution with Te elements at anion sites can effectively regulate the carrier characteristics of the system, causing a shift in the material's conductivity from n-type to p-type, and contributing to an improvement in the material's power factor (PF). In addition, the introduction of Se can effectively suppress the precipitation of the second phase; while the co-doping of S can adjust the ratio of the slip energy barrier to the cleavage energy of the material, which is the key driving force for stimulating the system to produce a significant "brittle-plastic" transition and obtain room temperature metallic ductility.
[0022] Therefore, by synergistically dissolving S, Se, and Te chalcogens in a specific ratio in a silver-copper matrix, on the one hand, the n-type to p-type transformation can be achieved and the electrical transport performance optimized; on the other hand, the present invention regulates the crystal structure and phase structure of the system through the synergistic design of multiple anion and cation sites, which not only effectively reduces the lattice thermal conductivity of the material, but also provides a structural basis for the material to exhibit intrinsic plasticity at room temperature, laying the material foundation for achieving high-performance p-type thermoelectric conversion.
[0023] The present invention also provides a method for preparing the silver-copper based thermoelectric material described in the above technical solution, comprising: The raw materials were subjected to high-energy ball milling and sintering to obtain silver-copper based thermoelectric materials.
[0024] The present invention does not have any special limitations on the source of the raw materials, and commercially available products known to those skilled in the art can be used.
[0025] In this invention, the raw materials preferably include inorganic raw materials and process control agents.
[0026] In this invention, the inorganic raw materials are preferably elemental substances constituting the target product, pre-synthesized compound precursors, and mixtures of the above substances in any proportion.
[0027] In this invention, the preferred elemental substances are Ag, Cu, S, Se, and Te. There is no particular limitation on the amount of the elemental substance used; it can be weighed according to the stoichiometric ratio of the general chemical formula.
[0028] In this invention, the purity of the inorganic raw material is preferably ≥99%; the morphology of the inorganic raw material is preferably powder, flake, block, strip or sphere, more preferably powder; when the morphology of the inorganic raw material is powder, the particle size of the inorganic raw material is preferably 2~100 μm.
[0029] In this invention, the process control agent preferably comprises one of anhydrous ethanol, methanol, n-hexane, and benzene; the mass of the process control agent is preferably 0.1-20% of the total mass of the inorganic raw materials. As one embodiment, the mass of the process control agent can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, or 19% of the total mass of the inorganic raw materials.
[0030] In this invention, the high-energy ball milling method is preferably a planetary ball mill, a vibratory ball mill, a stirring ball mill, or a drum ball mill.
[0031] In this invention, the ball-to-material ratio of the high-energy ball mill is preferably (5~30):1; the rotation speed of the high-energy ball mill is preferably 100~2000 rpm; the single-run time of the high-energy ball mill is preferably 5~200 min; the cooling interval time of the high-energy ball mill is preferably ≤60 min; and the total ball milling time of the high-energy ball mill is preferably 2~100 h. In one embodiment, the ball-to-material ratio of the high-energy ball mill can be 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, or 29:1; the rotational speed of the high-energy ball mill can be 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1425 rpm, 1500 rpm, 1600 rpm, or 1700 rpm. The high-energy ball mill can operate at 1800 rpm or 1900 rpm; the single run time of the high-energy ball mill can be 10 min, 30 min, 50 min, 100 min or 150 min; the cooling interval of the high-energy ball mill can be 10 min, 15 min, 20 min, 30 min, 40 min or 50 min; and the total ball milling time of the high-energy ball mill can be 10 h, 20 h, 22.5 h, 30 h, 40 h, 50 h, 60 h, 70 h, 80 h or 90 h.
[0032] In this invention, the grinding balls and grinding jars used in the high-energy ball mill are preferably made of at least one of stainless steel, cemented carbide, zirconium oxide and agate, and more preferably cemented carbide.
[0033] In this invention, the grinding balls used in the high-energy ball milling preferably include large balls and small balls; the particle size ratio of the large balls to the small balls is preferably (1.3~3):1; the particle size of the large balls is preferably 8~15 mm, more preferably 11.9 mm; the particle size of the small balls is preferably 3~7 mm, more preferably 6.35 mm; the number ratio of the large balls to the small balls is preferably 1:(1~8), more preferably 1:3. In the non-thermal equilibrium solid-phase synthesis process, this invention specifically employs a high-energy ball milling strategy that uses complementary ratios of large and small balls. The particle size of the large balls is controlled at 8~15 mm, mainly used to generate strong macroscopic impact energy at high speeds, thereby driving lattice distortion in highly ductile metals such as Ag and Cu and initiating atomic-level in-situ solid-phase reactions; the particle size of the small balls is controlled at 3~7 mm. The high spatial distribution frequency and collision probability of the large and small balls within the grinding jar provide a larger effective contact area for low-energy friction and shearing, which helps to promote the efficient refining and uniform dispersion of volatile chalcogen elements (S, Se, Te). Studies have shown that by precisely limiting the ratio of large to small balls to 1:(1~8), the collision and shearing probability inside the grinding jar can achieve a better dynamic balance. When the ratio of large to small balls is set to around 1:3, the energy generated by the large balls is sufficient to cause solid-phase reactions of various elements, while the small balls can, to a certain extent, buffer and regulate the local impact stress released by the large balls. This spatial distribution design, while accelerating the multi-element reaction rate, combined with the use of process control agents, helps to significantly reduce the tendency of powder to cold weld agglomerate and stick to the jar under single-size grinding balls, providing a reliable process guarantee for obtaining solid solution powders with relatively pure phase structure and relatively uniform component distribution.
[0034] In one implementation, the particle size ratio of the large spheres to the small spheres can be 1.5:1, 1.87:1, 2:1, or 2.5:1.
[0035] In this invention, the high-energy ball milling is preferably carried out in a protective atmosphere; the protective atmosphere is preferably one of argon, helium and nitrogen, and more preferably argon.
[0036] After high-energy ball milling, the product obtained by high-energy ball milling is preferably cooled. The cooling operation is not particularly limited in this invention; any operation well-known to those skilled in the art can be used to cool to room temperature.
[0037] In this invention, the sintering is preferably hot pressing sintering or spark plasma sintering; the sintering is preferably carried out in a vacuum or protective atmosphere; the protective atmosphere is preferably one of argon, helium and nitrogen.
[0038] The present invention does not impose any special limitation on the vacuum degree of the vacuum; any vacuum conditions well known to those skilled in the art can be used.
[0039] In this invention, the contact surface between the sintering mold and the sample to be sintered is provided with an insulating medium; the insulating medium is preferably boron nitride or mica. In this invention, the insulating medium is used to form electrical isolation between the sample and the mold. As long as it can prevent the sintering current from directly penetrating the sample to achieve the insulation effect, it is not necessary to strictly limit the complete coverage of the raw material.
[0040] In this invention, the sintering temperature is preferably 200~600℃; the sintering pressure is preferably 10~100MPa; the holding time for sintering is preferably 5~100 min; and the rate of heating to the sintering temperature is preferably 0.5~20℃ / s. As one embodiment, the sintering temperature can be 300℃, 350℃, 400℃, 450℃, 500℃, or 550℃; the sintering pressure can be 20 MPa, 30 MPa, 40 MPa, 50 MPa, 60 MPa, 70 MPa, 80 MPa, or 90 MPa; the holding time for sintering can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, or 90 min; and the rate of heating to the sintering temperature can be 1℃ / s, 5℃ / s, 10℃ / s, or 15℃ / s. This invention utilizes sintering to achieve densification of thermoelectric materials.
[0041] In this invention, the sintering is preferably performed using a graphite mold and / or an alloy mold, more preferably a graphite mold.
[0042] To address the problems of element volatility, high system sensitivity to thermal processes, high energy consumption, and long cycle times in the preparation of such materials using existing high-temperature melting processes, this invention proposes a solid-state synthesis scheme based on high-energy ball milling: raw materials are mixed in stoichiometric proportions and then ball-milled under a protective atmosphere. This preparation method utilizes mechanically driven multi-element solid-state reactions, avoiding element volatilization caused by high temperatures and second-phase precipitation caused by temperature fluctuations, while significantly shortening the preparation cycle. This invention features a short preparation cycle, low energy consumption, and precise controllable product composition. It also achieves effective regulation of p-type thermoelectric transport properties and room-temperature plasticity within the system, demonstrating potential for large-scale mass production.
[0043] The beneficial effects of this invention are as follows: 1. This invention is based on Ag 2-x Cu x S 1-y-z Se y Te zThe introduction of Cu at the cation sites in the system lays a crucial material foundation for precise control of conductivity type. Unlike the n-type conductivity of traditional Ag₂Q-based materials, this invention provides a source of hole carriers by introducing Cu, and combines this with the proportion of anion site components (i.e.,...) x , y , z By precisely controlling the values of Cu, the conductivity type of the system was successfully transformed into p-type. Furthermore, within a specific ratio range, the system can also exhibit n-type characteristics. The introduction of Cu and the synergistic alloying of multiple elements successfully broadened the conductivity types of this type of material, enabling the reliable preparation of p-type thermoelectric materials.
[0044] 2. This invention is based on Ag 2-x Cu x S 1-y-z Se y Te z S, Se, and Te multi-element co-doping at the anion sites in the system enables effective control of phase purity, thermoelectric transport, and room temperature plasticity.
[0045] (1) The incorporation of Se can effectively suppress the precipitation of the second phase (AgCuTe cannot exist stably at room temperature due to phase separation, while the introduction of trace amounts of Se into AgCuTe can effectively obtain a pure phase structure), thereby ensuring the purity of the matrix phase of the material and avoiding the damage of impurities to the overall mechanical and transport properties of the material.
[0046] (2) The incorporation of Te is not only an important means of optimizing the thermoelectric properties of materials, but also a core element that dominates the macroscopic conductivity type of the system. With the introduction of Cu at the cation sites as a foundation, by appropriately increasing the proportion of Te at the anion sites, the carrier characteristics of the system can be successfully controlled, driving the conductivity type of the material to undergo a key transformation from n-type to p-type (for example, in a certain pseudo-quaternary solid solution, steady-state p-type conduction can be achieved when the proportion of Te exceeds a certain phase boundary). At the same time, the design of a high Te proportion helps to further optimize the band structure and electrical transport characteristics of the system, so that the high ZT value of the material is mainly concentrated in the component range with higher Te content.
[0047] (3) Trace doping of sulfur plays a crucial driving role in imparting intrinsic room-temperature plasticity to the matrix material. Studies have shown that undoped multi-element matrices typically exhibit brittle fracture characteristics, while the introduction of a specific proportion of sulfur can effectively adjust the ratio of the mechanical slip energy barrier to the cleavage energy, thereby stimulating the "brittle-plastic" transition in the system. In addition, the incorporation of sulfur also helps to suppress the precipitation of the second phase to some extent.
[0048] 3. Addressing the tendency of chalcogen elements (S, Se, Te) in multi-element silver-copper based systems to readily volatilize and be lost at high temperatures, this invention employs a closed-loop high-energy ball milling process to replace the traditional high-temperature smelting technique. This non-thermal equilibrium solid-phase synthesis route avoids the high-temperature liquid environment of traditional processes, effectively preventing the loss of volatile elements in the high-temperature liquid state and ensuring the consistency between the actual chemical composition of the final alloyed powder and the designed stoichiometric ratio.
[0049] 4. Existing high-temperature melting processes for preparing multi-element doped materials pose a risk of localized component segregation and second-phase precipitation due to temperature fluctuations during heat treatment, thereby impairing the overall performance of the material. This invention, based on high-energy mechanical work-driven solid-state reactions, successfully avoids the complex liquid-solid phase transition and subsequent stringent heat treatment processes. It effectively reduces interference from temperature gradients, promotes the uniform distribution of multiple dopants, and significantly reduces the risk of component segregation and second-phase precipitation, thus ensuring the consistency of the material's microstructure and its macroscopic mechanical plasticity.
[0050] 5. Existing smelting processes for preparing such materials typically require high-temperature reactions (around 1100°C) lasting several days, followed by rigorous and prolonged heat treatment, resulting in high energy consumption and long production cycles. The high-energy ball milling and sintering process provided by this invention effectively simplifies the operation. By avoiding the traditional high-temperature melting and solidification processes, the overall energy consumption is significantly reduced, and the production cycle for a single batch is drastically shortened from several days in traditional processes to several hours. Furthermore, this solid-state synthesis process offers a large parameter adjustment range and good batch-to-batch repeatability, providing a reliable technical foundation for the transition of high-performance multi-element doped plastic thermoelectric materials from gram-level laboratory preparation to industrial-scale, low-cost mass production.
[0051] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0052] The compression performance of the samples was tested using a universal testing machine (room temperature, sample size 3×3×6 mm, pressurization rate 0.1 mm / min); the thermoelectric properties were tested using an electrical performance testing device and a laser thermal conductivity meter (ZT value, protective atmosphere, electrical conductivity sample size 2×2×11 mm, thermal conductivity sample size 12.7 mm in diameter and 1 mm in thickness; test temperature points: room temperature 30℃, 50℃ and 70℃); the phase distribution of the samples was characterized using scanning electron microscopy and elemental composition analysis was performed using EDS.
[0053] Example 1 The general chemical formula for silver-copper based thermoelectric materials is AgCuSe; The preparation method of the silver-copper-based thermoelectric material is as follows: (1) According to the molar ratio of Ag:Cu:Se of 1:1:1, weigh 3.2360 g of Ag powder, 1.9064 g of Cu powder and 2.3688 g of Se powder, totaling 7.5112 g of single raw materials. Weigh 0.3756 g (5% of the total mass of single raw materials) of anhydrous ethanol as a process control agent. Weigh 150.2259 g (ball-to-material ratio of 20:1) of cemented carbide grinding balls (hRC60-65, high carbon chromium bearing steel). The purity of Ag powder, Cu powder and Se powder is 99.99% and the particle size is 2~100 μm. The grinding balls are composed of large balls and small balls. The particle size of the large balls is 11.9 mm. The particle size of the small balls is 6.35 mm. The ratio of the number of large balls to small balls is 1:3. (2) In a glove box filled with argon, the grinding balls, elemental raw materials and process control agent are sequentially assembled into the ball milling jar, and the ball milling jar is sealed. The ball milling program is set to a single working time of 30 min and a single cooling time of 15 min, with a total of 45 min as one cycle. 30 cycles are run, the ball milling time is 15 h, the total time is 22.5 h, the rotation speed is 1425 rpm, and then the mixture is cooled to room temperature and the alloyed powder is taken out. (3) The alloyed powder is loaded into a graphite mold (compressive strength 130 MPa, mold inner diameter 12.7 mm), and subjected to discharge plasma sintering under an argon atmosphere of 60 MPa and 500℃ for 10 min to obtain silver-copper based thermoelectric material; wherein, the inner cavity sidewall, upper pressure head, lower pressure head and the surface of the sample to be sintered of the sintering mold are all provided with insulating medium mica.
[0054] Example 2 The general chemical formula for silver-copper based thermoelectric materials is AgCuSe. 0.8 Te 0.2 The purity of the Te powder was 99.99%, the particle size was 2~100μm, and other conditions were the same as in Example 1.
[0055] Example 3 Based on Example 2, the general chemical formula was modified to AgCuSe. 0.6 Te 0.4 The quality of Ag powder, Cu powder, Se powder, and Te powder can be modified to suit different conditions.
[0056] Example 4 Based on Example 2, the general chemical formula was modified to AgCuSe. 0.4 Te0.6 The quality of Ag powder, Cu powder, Se powder, and Te powder can be modified to suit different conditions.
[0057] Example 5 Based on Example 2, the general chemical formula was modified to AgCuSe. 0.3 Te 0.7 The quality of Ag powder, Cu powder, Se powder, and Te powder can be modified to suit different conditions.
[0058] Example 6 Based on Example 2, the general chemical formula was modified to AgCuSe. 0.2 Te 0.8 The quality of Ag powder, Cu powder, Se powder, and Te powder can be modified to suit different conditions.
[0059] Example 7 Based on Example 2, the general chemical formula was modified to AgCuSe. 0.1 Te 0.9 The quality of Ag powder, Cu powder, Se powder, and Te powder can be modified to suit different conditions.
[0060] Example 8 Based on Example 2, the general chemical formula was modified to AgCuTe, and the masses of Ag powder, Cu powder, Se powder and Te powder were modified accordingly, while other conditions remained unchanged.
[0061] The performance of the silver-copper based thermoelectric materials prepared in Examples 1-8 was tested, and the results are shown in Table 1.
[0062] Table 1 Performance data of the silver-copper based thermoelectric materials prepared in Examples 1-8
[0063] As shown in Table 1, with the increase of Te content in the system (i.e., when the molar percentage of Te is in the range of 0.4 to 0.6), the Seebeck coefficient of the material reverses from negative to positive, indicating that the conductivity type of the system has successfully changed from n-type to p-type. In the corresponding p-type conductivity region (Te molar percentage of 0.6 to 0.9), the room temperature ZT value of the sample gradually increases with the increase of Te content, reaching a peak value near the ratios of 0.8 and 0.9. It is worth noting that the end-member component AgCuTe is thermodynamically unstable at room temperature (easily undergoing spontaneous phase separation and decomposing into two phases), leading to the deterioration of its internal microstructure and thus causing a significant decrease in the macroscopic ZT value.
[0064] BSE image of the silver-copper based thermoelectric material prepared in Example 7 is shown below. Figure 1 As shown; EDS surface scan image of the silver-copper based thermoelectric material prepared in Example 7 is shown below. Figure 2 As shown; the XRD patterns of the silver-copper based thermoelectric materials prepared in Examples 7-8 are as follows. Figure 3 As shown. Multi-point EDS composition analysis was performed on the silver-copper based thermoelectric material prepared in Example 7, and the average value was taken. The results are as follows. Figure 4 As shown.
[0065] from Figures 1-2 It can be seen that Se doping effectively eliminates the second phase in the matrix, resulting in a uniform single-phase microstructure. Simultaneously, EDS surface scan results confirm that the constituent elements are highly uniformly distributed in the matrix, with no component segregation. Further combined with… Figure 3 XRD pattern analysis showed that the alloying of Se significantly improved the phase stability of the AgCuTe system, and the diffraction peaks of the original impurity phases were completely suppressed, confirming that Se played a key role in phase purification of the system.
[0066] from Figure 4 It can be seen that the actual atomic percentages of the silver-copper based thermoelectric material are Ag 33.11%, Cu 32.88%, Se 3.96%, and Te 30.05%. This result is consistent with the AgCuSe... 0.1 Te 0.9 The calculated theoretical atomic percentages (Ag 33.33%, Cu 33.33%, Se 3.33%, Te 30.00%) have very small errors, indicating that the actual chemical composition of the prepared sample is highly consistent with the designed nominal ratio.
[0067] Backscattered electron (BSE) image of the silver-copper based thermoelectric material prepared in Example 8 is shown below. Figure 5 As shown.
[0068] from Figure 5 It can be seen that the silver-copper based thermoelectric material exhibits a clear two-phase separation state at room temperature.
[0069] Example 9 Based on Example 7, only a large ball is used, while other conditions remain unchanged.
[0070] Example 10 Based on Example 7, the ratio of large balls to small balls was modified to 1:6, while other conditions remained unchanged.
[0071] Example 11 Based on Example 7, only small balls are used, while other conditions remain unchanged.
[0072] The performance data of the silver-copper based thermoelectric materials prepared in Examples 7 and 9-11 are shown in Table 2.
[0073] Table 2 Performance data of the silver-copper based thermoelectric materials prepared in Examples 7 and 9-11
[0074] As shown in Table 2, based on Example 7, only the number of grinding balls was adjusted, while keeping the ball-to-material mass ratio at 20:1 and other process parameters unchanged. A comparison of the data reveals that when the grinding balls consisted only of large balls (Example 9) or only of small balls (Example 11), the room temperature ZT values of the samples were relatively low, at 0.33 and 0.30 respectively, and only 0.48 and 0.43 at 70°C. This indicates that single-size grinding media may have certain limitations in solid-state synthesis. In contrast, the introduction of a large-to-small ball gradation strategy resulted in a significant optimization trend in material properties: Example 10 (number ratio 1:6) maintained a ZT value of 0.32 at room temperature, but its ZT value increased to 0.52 at 70°C; while Example 7 (number ratio 1:3) exhibited relatively better electrothermal transport characteristics, with ZT values as high as 0.50 at room temperature and 0.70 at 70°C.
[0075] The above results indicate that a reasonable combination of large and small balls can improve the overall thermoelectric properties of the material. Therefore, the grinding balls provided by this invention have a ratio of large balls to small balls of 1:(1~8), preferably 1:3.
[0076] Example 12 The general chemical formula for silver-copper based thermoelectric materials is AgCuS. 0.08 Se 0.22 Te 0.7 ; The preparation method of the silver-copper-based thermoelectric material is as follows: The elemental raw materials were accurately weighed according to the stoichiometric ratio: Ag 2.8868 g, Cu 1.7006 g, S 0.0686 g, Se 0.4649 g, and Te 2.3904 g. The ball milling time was modified to 9 h, i.e., 20 cycles were run. Other conditions were the same as in Example 1.
[0077] Example 13 Based on Example 12, the ball milling time was modified to 15 hours, i.e., 30 cycles were run, while other conditions remained unchanged.
[0078] Example 14 Based on Example 12, the ball milling time was modified to 30 hours, i.e., 60 cycles were run, while other conditions remained unchanged.
[0079] The compressibility of the silver-copper based thermoelectric material prepared in Example 14 is 22%.
[0080] Example 15 Based on Example 12, the ball milling time was modified to 45 hours, i.e., 90 cycles were run, while other conditions remained unchanged.
[0081] The performance data of the silver-copper based thermoelectric materials prepared in Examples 12-15 are shown in Table 3.
[0082] Table 3 Performance data of the silver-copper based thermoelectric materials prepared in Examples 12-15
[0083] As shown in Table 3, within this process window, the sample treated with a cumulative ball milling time of 30 h exhibits better thermoelectric transport properties, with a peak ZT value of approximately 0.15 at 70 °C. Therefore, for the five-element multi-element doped system described in this invention, the ball milling time is preferably 30 h.
[0084] Example 16 The general chemical formula for silver-copper based thermoelectric materials is AgCuS. 0.05 Se 0.1 Te 0.85 The weighing mass of inorganic raw materials of Ag, Cu, S, Se and Te elements is adjusted accordingly according to the stoichiometric ratio; other conditions are the same as in Example 14.
[0085] Figure 6 BSE image of the silver-copper based thermoelectric material prepared in Example 16; Figure 7 This is an EDS surface scan image of the silver-copper based thermoelectric material prepared in Example 16.
[0086] from Figure 6 and 7 It can be seen that no obvious second-phase contrast was observed inside the silver-copper-based thermoelectric material, exhibiting a good single-phase microstructure; and the constituent elements are highly uniformly distributed in the matrix, with no obvious component segregation. Tests showed that this silver-copper-based thermoelectric material exhibits good thermoelectric transport properties at room temperature, with a room temperature ZT value reaching 0.45.
[0087] Comparative Example 1 The general chemical formula for silver-copper based thermoelectric materials is AgCuSe. 0.1 Te 0.9 ; The preparation method is as follows: Each element was precisely weighed according to a predetermined stoichiometric ratio and placed into a quartz tube lined with a thin layer of pyrolytic carbon and vacuum sealed. The tube was gradually heated to 500°C over 12 hours to minimize sulfur evaporation, then heated to 1000°C over 5 hours and held at this temperature for 48 hours. Subsequently, the tube was cooled to 600°C for more than 4 hours, annealed at this temperature for 3 days, and then quenched in ice water. After cooling in liquid nitrogen, the material was ground into powder using an agate mortar. The powder was then placed into a 12.7 mm graphite mold and sintered under vacuum at 500°C for 5 minutes using an SPS system at a pressure of approximately 4.0 kN.
[0088] The sample prepared in Comparative Example 1 was a non-pure phase, while the sample prepared in Example 7 was a pure phase.
[0089] Comparative Example 2 The general chemical formula for silver-copper based thermoelectric materials is AgCuS. 0.05 Se 0.1 Te 0.85 The preparation method is the same as that of Comparative Example 1.
[0090] The ZT value of the sample prepared in Comparative Example 2 was only 0.33 at 70°C, which was lower than the ZT value at room temperature in Example 16.
[0091] As can be seen from the above embodiments and comparative examples, the silver-copper based thermoelectric material provided by the present invention has excellent thermoelectric properties.
[0092] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A silver-copper based thermoelectric material with the general chemical formula Ag. 2-x Cu x S 1-y-z Se y Te z ,in, 0< x <2;0≤ y ≤1;0≤ z ≤1;0< y + z ≤1。 2. The silver-copper based thermoelectric material according to claim 1, characterized in that, The x The value is 0.5~1.
5.
3. The silver-copper based thermoelectric material according to claim 1, characterized in that, The z Greater than 0 and less than 1.
4. A method for preparing the silver-copper based thermoelectric material according to any one of claims 1 to 3, comprising: The raw materials were subjected to high-energy ball milling and sintering to obtain silver-copper based thermoelectric materials.
5. The preparation method according to claim 4, characterized in that, The raw materials include inorganic raw materials and process control agents.
6. The preparation method according to claim 4, characterized in that, The grinding balls used in the high-energy ball mill include large balls and small balls; the particle size ratio of the large balls to the small balls is (1.3~3):
1.
7. The preparation method according to claim 6, characterized in that, The ratio of the number of large balls to the number of small balls is 1:(1~8).
8. The preparation method according to claim 6, characterized in that, The large spheres have a particle size of 8-15 mm; the small spheres have a particle size of 3-7 mm.
9. The preparation method according to claim 4, characterized in that, The sintering includes hot pressing sintering or spark plasma sintering.
10. The preparation method according to claim 4, characterized in that, The sintering mold used in the sintering process has an insulating medium on the contact surface between it and the sample to be sintered.